Conflict Of Interests In Social Development And The Worldview Of Young People - Akhmadiyev Nuriddin Mukhutdinovich (Periodica Journal, 2025)
In the spiritual and educational reform of society, the principle of effective use of the experience of conflicts of interest, full of deep knowledge and life lessons, is gaining special priority. From this point of view. It should be noted that today there is a noticeable increase in the participation of representatives of the older generation in the development of spheres and sectors of the world's population. In particular, the conflict of interest occupies an important place in the activity of the spiritual, educational, and upbringing process, in solving social problems encountered in the process of renewal and changes in society, and serves as the basis for studying it as an object of research. The problem of social development and the conflict of interests in the worldview of young people, the task of improving the mechanisms for the effective use of scientific potential in the formation of the moral culture of youth increases the need for research based on methodological approaches
Keywords: social development; conflict of interest; youth spirituality